Optimalisasi Throughput Pada Penerapan Load Balancing Dalam Jaringan Cloud Menggunakan Round Robin dan Least Connection - Erkamim, Moh.; Prihatin, Titin; Saraswati, Sandra Dewi; Tonggiroh, Mursalim (Journal of System and Computer Engineering, 2024)
As the complexity of cloud infrastructure increases, one of the main challenges faced is how to optimize throughput in cloud networks. Optimal throughput is crucial to guarantee the performance of applications and services hosted in the cloud. Using load balancing techniques can optimize throughput, but careful analysis and testing is needed regarding the appropriate load balancing approach to improve throughput performance. This research aims to analyze the effectiveness of load balancing strategies with Round Robin and Least Connection in increasing throughput in cloud networks. Through empirical testing, this study compares the two methods based on the resulting throughput at various connection levels, ranging from 1000/600 to 5000/1000. Test results show that both strategies provide similar performance at low connection rates, with Round Robin recording slightly higher throughput at 1000/600. However, the difference becomes almost imperceptible as the number of connections increases. At 2000/700 to 5000/1000, the throughput generated by both strategies shows marginal differences, with Least Connection slightly superior at the highest connection level. These findings indicate that both Round Robin and Least Connection can be applied effectively to increase throughput in cloud environments, with the selection of specific strategies depending on workload characteristics and service requests. This research provides valuable insights for academics and IT practitioners who want to optimize cloud networks to achieve maximum performance